Closed-Loop Frontal Midlineθ Neurofeedback: A Novel Approach for Training Focused-Attention Meditation - Brandmeyer, Tracy; Delorme, Arnaud (Frontiers in Human Neuroscience, 2020)
Cortical oscillations serve as an index of both sensory and cognitive processes and represent one of the most promising candidates for training and targeting the top-down mechanisms underlying executive functions. Research findings suggest that theta (θ) oscillations (3-7 Hz) recorded over frontal-midline (FMθ) electrodes are broadly associated with a number of higher-order cognitive processes and may serve as the mechanistic backbone for cognitive control. FMθ has also been shown to inversely correlate with activity in the default mode network, a network in the brain linked to spontaneous thought processes such as mind-wandering and rumination. Our previous research found the presence of increased FMθ oscillations in expert meditation practitioners during reported periods of focused-attention meditation practice, when compared to periods of mind-wandering. In an effort to narrow the explanatory gap by connecting these neurophysiological features to the phenomenological nature of experience, we designed a methodologically novel and adaptive neurofeedback protocol with the aim of modulating FMθ while having meditation novice participants implement breath-focus strategies derived from focused-attention mediation practices. Participants who received the adaptive FMθ-meditation neurofeedback protocol were able to significantly modulate FMθ over frontal electrodes across eight sessions relative to their performance in session one. Neurofeedback recipients also showed significantly faster reaction times on the n-back working memory task assessed before and after the FMθ-meditation neurofeedback protocol. No significant differences in frontal theta activity or behavior were observed in the active control participants who received age and gender matched sham neurofeedback.